From Debris Field to 1st Punic War Battle Map: Site Formation in the Egadi Battle Zone. (2nd January 2021) - Murray, William M.; Robb, George
ABSTRACT: On 10 March 241 BC the last naval battle of the 1st Punic War was fought off Sicily in the Aegates (modern Egadi) Island group. A large debris field on the sea-floor northwest of Levanzo Island is clearly the result of the battle between Rome and Carthage. In a controlled experiment, replica artefacts were dropped into the sea over the battle zone and their movements tracked to reveal certain aspects of the site's formation. The experiment's results explain the spatial relationships between some of the artefacts and suggest that many Greco-Italic amphoras may have been filled with grain.